Working or breastfeeding? Beyond good intentions - Oyola-García, Alfredo Enrique (2015)
In a recent study conducted in our country and published by Espinoza et al. (1) it is reported that the place of residence, natural region, mother's education, wealth index and antenatal associated to the abandonment of exclusive breastfeeding. Specifically, mothers who have left this practice are those living on the coast and in urban areas, which have better levels of education and higher incomes and, surprisingly, when they have six or more prenatal visits. We know that the higher the level of education improves the chances of access to decent employment and therefore a better labor income (2). Also, in the female population in urban areas and on the east coast of instruction--level indicator it shows better result than in rural areas or other natural regions (3) and therefore better opportunity to access working market.